The current epidemic status and prevention and control of bovine viral diarrhea virus in yaks in China - Li, Zhi; Han, Yuan; Yuan, Qing; Wang, Shuqin; Chen, Changjiang; Gao, Shandian; Meng, Ru (Frontiers in Cellular and Infection Microbiology, 2025)
In China, yaks are predominantly distributed across the Qinghai-Tibet Plateau and surrounding high-altitude regions, including Tibet, Qinghai, Sichuan, Gansu, Xinjiang and Yunnan. These animals serve as multifunctional resources for local herders, providing meat, dairy, hides, and wool, while also constituting a critical component of the industrial chain in high-altitude ecosystems. Recent epidemiological studies have demonstrated an increasing trend in bovine viral diarrhea virus (BVDV) infection rates among yak populations in provinces such as Gansu, Sichuan, Tibet, and Qinghai. This review not only summarizes the epidemiological status, distribution of viral sub-genotypes, and current prevention and control in yaks across various regions, but also proposes, for the first time, a systematic “Five-dimensional Integration” comprehensive prevention and control model for BVDV, including vaccine breakthrough, precise monitoring, dynamic early warning, population purification, and active prevention, which will provide directed insight for the prevention and control strategies of yaks infected by BVDV.